2020
DOI: 10.1097/md.0000000000018802
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of mirabegron on overactive bladder induced by benign prostatic hyperplasia in men receiving tamsulosin therapy

Abstract: Background: We conducted a meta-analysis to assess the efficacy and safety of mirabegron on overactive bladder (OAB) induced by benign prostatic hyperplasia (BPH) in men receiving tamsulosin therapy. Methods: We performed the analysis by using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The databases including MEDLINE, EMBASE, and the Cochrane Controlled Trials Register were retrieved to get information regarding randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“… Kaplan et al (2020) also found that the increase in PVR upon combination therapy is not statistically significant. However, the analyses by Su et al (2020) and Ichihara et al (2015) identified that the combined use will cause the average volume change of PVR to be significantly higher than that of tamsulosin (AB) alone. Pairwise meta-analysis in this study suggested a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“… Kaplan et al (2020) also found that the increase in PVR upon combination therapy is not statistically significant. However, the analyses by Su et al (2020) and Ichihara et al (2015) identified that the combined use will cause the average volume change of PVR to be significantly higher than that of tamsulosin (AB) alone. Pairwise meta-analysis in this study suggested a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…§: between mirabegron-treated and saline-treated rats (P = 0.066). Data are represented as mean ± SD, a Student's t test risk of increasing urinary retention [20]. In a randomized trial [21], add-on mirabegron while receiving tamsulosin with BPH, associated with increasing the PVR (mean change 14.7 mL, 95% CI 8.5, 21.0 mL).…”
Section: Discussionmentioning
confidence: 99%
“…Men with benign prostatic hyperplasia may have OAB in the form of concomitant lower urinary tract bladder storage symptoms, such as frequent micturition and nocturia. 55,56 Results from studies of antimuscarinics (eg, tolterodine ER) 57 and a b3-adrenergic agonist (ie, mirabegron) 58 alone or in combination with standard therapy for benign prostatic hyperplasia have shown improvement in these symptoms.…”
Section: Benign Prostatic Hyperplasia and Oabmentioning
confidence: 99%